On some integral inequalities for (h, m)-convex functions - Matłoka, Marian (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
In this paper we establish several Hadamard type inequalities for (h, m) convex functions.
Mathematical Economics, 2013, Nr 9 (16), s. 55-70
Keywords: Hadamard’s inequality; convex function